Maritime Trade and State Development in Early Southeast Asia - Hall, Kenneth R. (University of Hawai'i Press, 1985)
This book brings something new in both dimension and detail to our understanding of Southeast Asia from the first to the fourteenth centuries. It puts Southeast Asia in the context of the international trade that stretched from Rome to China and draws upon a wide range of recent scholarship in history and the social sciences to redefine the role that this trade played in the evolution of the classical states of Southeast Asia. By examining the sources of Southeast Asia's classical era with the tools of modern economic history, the author shows that well-developed socioeconomic and political networks existed in Southeast Asia before significant foreign economic penetration took place. With the growth of interest in Southeast Asian commodities and the refocusing of the major East-West commercial routes through the region during the early centuries of the Christian era, internal conditions within Southeast Asia adjusted to accommodate increased external contacts. Hall takes the view that Southeast Asia's response to international trade was a reflection of preexisting patterns of trade and statecraft. In the forty years since Coede's monumental work The Indianized States of Southeast Asia was published, a great deal of archaeological and epigraphical work has been done and new interpretations advanced. By integrating new theoretical constructs, recent archaeological finds and interpretations, and his own informed reading and research, Kenneth R. Hall puts his historical narrative on a large canvas and treats areas not previously brought together for discussion along comparative lines. Like Coedes' work, his book will be important as a basic text for the teaching of early Southeast Asian history.